The Boo Crew Needs You! - Fang, Vicky; Lu, Saiorse (Naperville, Illinois : Sourcebooks Jabberwocky, 2023)
An interactive picture book in which readers help the Book Crew -- a ghost, skeleton, and vampire-- fix various problems that get in the way of Halloween night fun.
Keywords: Stories in rhyme; Halloween -- Fiction; Monsters -- Fiction; Helpfulness -- Fiction; Stories in rhyme; Halloween -- Juvenile fiction; Stories in rhyme; Picture books